2021
DOI: 10.3390/children8050327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air Pollution on Obesity in Children: A Systematic Review and Meta-Analysis

Abstract: Air pollution exposure has been identified as being associated with childhood obesity. Nevertheless, strong evidence of such an association is still lacking. To analyze whether air pollution exposure affects childhood obesity, we conducted a systematic review and meta-analysis utilizing the PRISMA guidelines. Of 7343 studies identified, eight studies that investigated the effects of air pollutant characteristics, including PM2.5, PM10, PMcoarse, PMabsorbance, NOx, and NO2, on childhood obesity were included. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 46 publications
1
43
0
9
Order By: Relevance
“…In addition, a connection has been reported between chronic exposure to particle pollution and lead in blood, as well as uncommon common diseases [39] such as cleft lip and palate [40]. Similar studies outside the region have found a clear correlation between pollutants and obesity [41][42][43].…”
Section: Introductionmentioning
confidence: 81%
“…In addition, a connection has been reported between chronic exposure to particle pollution and lead in blood, as well as uncommon common diseases [39] such as cleft lip and palate [40]. Similar studies outside the region have found a clear correlation between pollutants and obesity [41][42][43].…”
Section: Introductionmentioning
confidence: 81%
“…Moreover, heavy traffic is also indicative of exposure to air-related pollution. Strong evidence on the association between exposure to air-related pollution, such as PM 2.5 , PM 2.5absorbance , PM 10 , PM coarse , NOx, and NO 2 , and the risk of childhood obesity was reported in a recent meta-analysis [ 19 ]. Other pathways potentially linking air-related pollution to obesity include increasing blood pressure [ 61 ], total cholesterol and LDL levels [ 62 ], and poor sleep [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, physical activity and/or sedentariness might serve as a pathway in which neighbourhood green space [ 12 , 13 ], safety [ 14 , 15 ], neighbourhood sidewalk [ 9 ], and local traffic [ 16 ] influence child weight status. By reducing harmful environmental stressors, such as air pollution, children benefit from living in greener [ 17 , 18 ] and low-traffic neighbourhoods [ 19 ] in relation to their healthy body weight. Moreover, the improvement in a positive emotional state might explain why exposure to neighbourhood green space [ 20 , 21 ] and safety [ 22 ] are important to prevent children gain excess weight.…”
Section: Introductionmentioning
confidence: 99%
“…Influences during the perinatal, infancy, and early childhood periods, sometimes called developmental programming [ 42 ], appear to influence childhood obesity in ways other than simple energy balance [ 43 , 44 , 45 ], including in utero exposure to famine [ 46 ], maternal prenatal weight [ 45 ], breastfeeding [ 47 ], numerous in utero exposures [ 44 ], antibiotic use early in life [ 48 ], dietary sugar intake [ 49 ], dietary intake of ultra-processed foods [ 50 ], infection with Adenovirus 36 [ 51 , 52 , 53 ], exposure to endocrine disruptors (e.g., chemicals in plastic bottles) [ 54 ], air pollution [ 55 ], food allergies [ 56 ], dysfunctional reward system in the orbitofrontal cortex [ 57 , 58 ], and even traditional medicinal plants [ 59 ]. The biological mechanisms by which each of these possible initiation factors influence the trajectory toward obesity are not clearly known, but must work through interrelationships with complex energy balance mechanisms.…”
Section: Discussionmentioning
confidence: 99%